Informational Provincial Center of Medical Sciences. A quarter of a century doing right to many. Day of the 25 anniversary. - María Elinor Dulzaides Iglesias; Ana María Molina Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
-